Arborine, a Larval Growth Inhibitor from Glycoslnis pentaphylla - Ahmad, Farediah; Mohd Ismail, Hazar; Rahmani, Mawardi (Universiti Putra Malaysia Press, 1994)
Arborine (I), a quinazolone alkaloid was isolated from the leaves of Glycosmis pentaphylla (Rutaceae) and was found to have a growth inhibitory effect on the larvae of Drosophila melanogaster.